2005
DOI: 10.1093/pubmed/fdi049
|View full text |Cite
|
Sign up to set email alerts
|

Unsafe driving in North American automobile commercials

Abstract: Unsafe driving is prevalent in North American automobile commercials. Given the extent to which MVCs are a public health and economic concern, this finding seems in conflict with responsible advertising. The degree to which the portrayal of driving in automobile commercials affects consumer-driving behaviour should be an area of further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 26 publications
1
21
0
1
Order By: Relevance
“…While we found no research on the direct influence of motor vehicle advertising on viewers' attitudes and intentions with respect to unsafe driving practices, a review of the literature suggests that themes used in motor vehicle advertising may promote and encourage speed and unsafe, risk taking behaviours among viewers, and particularly among those already vulnerable to engaging in impulsive, risk taking behaviours (Gardner and Steinberg, 2005;Pechmann et al, 2005;Chapman and Blows, 2003;Shin et al, 2005;Ferguson et al, 2003;Sofoulis et al, 2005;World Health Organization, 2004). For example, in relation to road safety, Sofoulis et al (2005) found that young people associated fast driving with fun and a 'buzz', and perceived that lack of vehicle control was due to bad driving rather than speed.…”
Section: Motor Vehicle Advertising and Marketingmentioning
confidence: 76%
See 4 more Smart Citations
“…While we found no research on the direct influence of motor vehicle advertising on viewers' attitudes and intentions with respect to unsafe driving practices, a review of the literature suggests that themes used in motor vehicle advertising may promote and encourage speed and unsafe, risk taking behaviours among viewers, and particularly among those already vulnerable to engaging in impulsive, risk taking behaviours (Gardner and Steinberg, 2005;Pechmann et al, 2005;Chapman and Blows, 2003;Shin et al, 2005;Ferguson et al, 2003;Sofoulis et al, 2005;World Health Organization, 2004). For example, in relation to road safety, Sofoulis et al (2005) found that young people associated fast driving with fun and a 'buzz', and perceived that lack of vehicle control was due to bad driving rather than speed.…”
Section: Motor Vehicle Advertising and Marketingmentioning
confidence: 76%
“…It is also common for ads targeting young people (and those who think they still are) to show an additional benefit of the owner being admired by a member of the opposite sex. These appeals are embedded in a variety of execution styles, which often include unsafe driving practices (Shin et al, 2005;Tamburro et al, 2004;Ferguson et al, 2003).…”
Section: Motor Vehicle Advertising and Marketingmentioning
confidence: 99%
See 3 more Smart Citations